Group portrait of the attendees of the Annual Summer Conference of the Evangelical Mission Covenant Churches of California - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of the attendees of the Annual Summer Conference of the Evangelical Mission Covenant Churches of California, held July 1938 in Santa Cruz, California. The group is assembled out of doors in front of several residential buildings.